Antibody Library Display on a Mammalian Virus Vector: Combining the Advantages of Both Phage and Yeast Display into One Technology - S. Smith, Ernest; Zauderer, Maurice (Current Drug Discovery Technologies, 2014)
Utilizing a vaccinia virus based library technology, we previously developed an antibody discovery platform that enabled efficient selection of fully functional IgG antibodies from highly diverse immunoglobulin gene libraries expressed on the surface of mammalian cells. Recently, we have further modified this platform to enable efficient expression of a library of fully human antibodies on the surface of vaccinia virus; an enveloped mammalian virus. Similar in concept to phage display, conditions are utilized under which each vaccinia virion expresses a single antibody specificity on its surface. Various panning and magnetic bead based methods have been developed to allow screening of a library of vaccinia- MAb virions and selection of recombinant vaccinia virus encoding specific antibodies. Upon infection of mammalian cells the antibody is not only incorporated into newly produced virus, it is also displayed on the surface of the host cell. Similar to methods utilized in yeast display, the cells displaying vaccinia encoded antibody can also be selected using a combination of magnetic beads and cell sorting, and the virus encoding the specific antibody heavy and light chains readily recovered and analyzed. This technology allows for rapid high throughput selection of vaccinia-MAb virions in a cell free panning system, followed by cell based screening for high specificity and fine selection of optimal antibodies.
Keywords: vaccinia virus